2016
DOI: 10.1007/s00192-016-3221-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre randomized trial of the Ajust™ single-incision sling compared to the Align™ transobturator tape sling

Abstract: At 1 year, the Ajust™ SIMS showed non-inferior effectiveness compared with the Align™ transobturator sling. Although not statistically significant, unexpectedly, more women reported persistent thigh pain in the Ajust™ group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The inclusion of women with MUI in our study certainly lowers the percentage of those reporting no leakage at all after the procedure, which was our primary outcome. In any case, the randomized design allows us to compare Ajust® with other slings with an established effect on incontinence, showing no significant difference, which is in agreement with the results of the other studies comparing Ajust® with TVT-O [7, 911, 13, 1517]. Our findings are also in accordance with the results of meta-analyses regarding patient-reported cure rates for both short- and long-term follow-up periods, when comparing conventional mid-urethral slings with SIMS all together and with Ajust separately [29], likewise when comparing SMUS with the group of adjustable SIMS [30].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The inclusion of women with MUI in our study certainly lowers the percentage of those reporting no leakage at all after the procedure, which was our primary outcome. In any case, the randomized design allows us to compare Ajust® with other slings with an established effect on incontinence, showing no significant difference, which is in agreement with the results of the other studies comparing Ajust® with TVT-O [7, 911, 13, 1517]. Our findings are also in accordance with the results of meta-analyses regarding patient-reported cure rates for both short- and long-term follow-up periods, when comparing conventional mid-urethral slings with SIMS all together and with Ajust separately [29], likewise when comparing SMUS with the group of adjustable SIMS [30].…”
Section: Discussionsupporting
confidence: 86%
“…The post-operative evaluation was carried out through a combination of interview and examination and the observed cure rate of 51.6% is in agreement with our results based on the ICIQ-UI-SF. However, the cure rates reported by the remaining studies evaluating the efficacy of Ajust® up to 2 years are significantly higher at around 85% [417]. On the other hand, the cure rate we observed of 71.1–82.9% based on the bladder diary was comparable with these studies and the same was observed for the percentage of women who reported being significantly/much better after both procedures, which was up to 95.1%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a previous trial (60 patients) comparing mini-slings (Ajust) with obturator tapes, 3 patients who received mini-slings reported persistent thigh pain 1 year after surgery, as compared with none who received obturator tapes. 22 In the Trial of Mid-Urethral Slings (597 patients), pain was more commonly reported with obturator tapes than with retropubic tapes (9.4% vs. 4.0%). 23 In the present trial, all 4 patients receiving tape removal for pain at up to 15 months were in the mini-sling group.…”
Section: Discussionmentioning
confidence: 99%
“…Data searches were performed in Google Scholar, PubMed, Medline, Embase, Scopus, Web of Science and the Cochrane Database of Systematic Reviews. Finally, 29 studies , including a total of 2 986 women, were selected for the meta‐analysis. An SIMS was defined as a midurethral sling placed through a single vaginal incision without skin incision, and included the Mini‐Arc, Contasure‐Needleless, Ophira, tissue fixation system (TFS) and Ajust.…”
Section: Methodsmentioning
confidence: 99%